The Perception of Hotel Operators on the use of Tie-dye Fabrics in Soft Furnishing of Hotel Interiors in Anaocha Local Government Area of Anambra State, Nigeria - Ifechukwu B. Nwadi; Lebechukwu C. Nwadi; Chiagozie U. Onuoha (International Journal of Home Economics, Hospitality and Allied Research)
The study investigated the perception of hotel operators on the use of tie-dye fabrics in soft furnishing of hotel interiors (PHOUTDFSFHI) in Anaocha LGA of Anambra State. Five research objectives and questions were formulated to guide the study. The population for the study comprised 100 respondents and there was no sampling since the population was small enough to be sufficiently managed. The study adopted a descriptive survey design. A structured questionnaire was used for data collection (0.76 Cronbach’s Alpha). Data collected were analyzed using mean and Standard Deviation. The major findings of the study revealed that choosing tie-dye fabrics made from durable and easy-to-maintain materials are measured for effective use of tie-dye fabrics in soft furnishing of hotel interiors. Hotel operators’ perception of tie-dye fabrics can serve as indicators of broader industrial trends and consumer preferences. The implication is that positive perception might signal growing interest in artisanal aesthetics within the hospitality sector, prompting hotels to adapt their design strategies accordingly. It was concluded that by fostering an environment that promotes a balanced engagement, recognizes creative efforts, and aligns performance metrics with employee satisfaction, hotels can ensure sustainable growth and competitive advantage. Among the recommendations made was that staff members should be trained on the cultural significance and craftsmanship behind tie-dye fabrics. This is to communicate its value to guests. Also, receiving feedback from guests about their experiences with tie-dye fabrics will help the business to adjust accordingly.